Pengaruh Sudut Blade Turbin Angin Poros Horizontal model Contra Rotating terhadap Daya dan Efisiensi dengan Posisi Rotor Blade saling Berseberangan - Laurensius Nogur; Verdy Ariyanto Koehuan; Jahirwan Ut Jasron (Jurusan Teknik Mesin, Fakultas Sains dan Teknik, Universitas Nusa Cendana, 2014)
Contra Rotating wind turbine is a horizontal axis turbine has two rotors rotating in opposite directions on the same axis giving and receiving power so that it can operate well at low wind speeds. In this study carried out by determining the variation in the angle of the blade, i.e. each angle of 0º, 5º, and 10º on the two rotors with a diameter of 0.50 m, respectively, and 0.30 m at a position opposing the rotor blade. The purpose of this study was to determine the effect of the variation of the rotation angle blade turbine (rpm), torque (T) and power coefficient (Cp) and the efficiency of the turbine at any wind speed variations. Wind speed influence on the output power or mechanical power, rotation of the rotor and the rotor thrust force, the lowest output power 7.396 watts at wind speed of 4,03 m/s, the highest Daya outputof 25.397 watts at wind speeds of 6,08 m/s, Round lowest rotor to 727 rpm with no load on the wind speed of 4.03 m/s at an angle of 0º blade, rotor rotation 1153 rpm ​​at the highest wind speed of 6,08 m/s at an angle blade10º. Rotor thrust 450 g at the lowest wind speed of 4.03 m/s at an angle of 0º, the highest 750 g rotor thrust on wind speed of 6,08 m/s at an angle of blade 10º. The change in the angle of the wind turbine blade shaft Contra rotating horizontal models, the power coefficient (Cp) generated from the turbine work increases with the angle with Cpmaks 0,701 at TSR 4.275 for 10º angle.